United Nations Model Double Taxation Convention between Developed and Developing Countries: 2017 Update - United Nations (United Nations, 2018)
The United Nations Model Double Taxation Convention between Developed and Developing Countries: 2017 Update is a publication geared towards the international community especially developing countries and countries with economies in transition. This new revision of the UN Model updates the widely used 2011 version of the Model. It is important for countries that seek assistance in the negotiation and implementation of modern bilateral double tax treaties reflecting their current circumstances and policy priorities. The Model recognizes that to avoid double taxation of investment, country where the investment takes place and country of the investor often share taxing rights. The Model helps to do it in a way that preserves an appropriate share of taxing rights to developing countries. The Model also promotes cooperation to deal with tax avoidance and evasion.